PENGARUH INTOLERANCE OF AMBIGUITY DAN KETERSEDIAAN DETAIL INFORMASI STRATEGI TERHADAP KEPUTUSAN MANAJER DALAM PROSES EVALUASI DENGAN BALANCED SCORECARD - , Shita Monika, Dr. Mahfud Sholihin, M. Acc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The motivation of this research is to replicate and extend the research of Lietdka et al. (2008). Lietdka et al. (2008) suggested for further research include the provision of detailed strategies information (Banker et al., 2004). Researchers wanted to test whether the availability of detailed of strategies information will affect the outcome evaluation by managers who are intolerant of ambiguity. This study uses the instrument of Lipe and Salterio (2000) which has been modified by Banker et al. (2004) and the design of experiments is 2x2 between subject. The results show that there is no difference between managers who are intolerant of ambiguity with the managers that are tolerant to ambiguity when detailed information strategies is not available